Sick child’s feeding practices and associated factors among mothers with sick children aged less than 2 years in Gamo zone, southern Ethiopia. Does the participation of fathers contribute to improving nutrition? A facility-based cross-sectional study - Hailu, Feven Masresha; Kefene, Simegn Wagaye; Sorrie, Muluken Bekele; Mekuria, Misgun Shewangezaw; Guyo, Tamirat Gezahegn (Frontiers in Public Health, 2023)
Background: Children's nutritional status can decline rapidly during or after common childhood illness unless additional nutritional requirements associated with illness are considered. Therefore this study was aimed at assessing sick child feeding practice and associated factors among mothers who have sick children aged less than two years in Southern Ethiopia.: A facilities-based cross-sectional study design was employed from April 1 to 30, 2022. Data were collected through the questionnaire entered into an open data kit (ODK) & exported in to Statistical Packages for Social Sciences (SPSS) version 25.0 for analysis. A systematic random sampling technique was used to select study participants. Bivariable and multivariable logistic regression analysis were used to identify factors associated with sick child feeding practice. An adjusted Odds ratio (AOR) with 95% confidence interval (CI) was used to determine the strength of association. Statistical significance was declared at p-value < 0.05.The overall magnitude of good sick child feeding practice of mothers was determined to be 45.0% (95% CI: 41.03%, 48.97%). Being urban residents, being employed, having antenatal Deleted: ¶